2004
DOI: 10.1590/s0103-97332004000100004
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of dynamical anomalies in stretched water

Abstract: In this work, we describe how the anomalous diffusivity is related to the structural anomalies. For this purpose, we study how the thermodynamics and the dynamics of low-temperature water are affected by the decrease of the density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Simulations have also shown that the rotational diffusion and relaxation times are lower in the hydration layer of small peptides, proteins and cells compared to the bulk [44]. In this studies, the evolution of the orientational relaxation time, integrated over the rotational auto-correlation function, is proportional to the translational diffusion coefficient [45,46].…”
Section: Resultsmentioning
confidence: 76%
“…Simulations have also shown that the rotational diffusion and relaxation times are lower in the hydration layer of small peptides, proteins and cells compared to the bulk [44]. In this studies, the evolution of the orientational relaxation time, integrated over the rotational auto-correlation function, is proportional to the translational diffusion coefficient [45,46].…”
Section: Resultsmentioning
confidence: 76%
“…The thermophysical properties investigated in this work include pressure ( P ), potential energy ( U ), residual isochoric heat capacity ( C V ,res ), viscosity (η), and diffusion coefficient ( D self ). Previous molecular simulation studies have investigated the thermophysical properties of stretched homogeneous water at similar conditions, and comparisons are made here to these earlier studies. To our knowledge, the thermophysical properties of two-phase bubbly water have not been investigated previously.…”
Section: Introductionmentioning
confidence: 90%
“…The density of the system increases about 15% when the system goes from ambient pressure to 500 MPa. It is known that this increase in density leads to a substantial increase of the average coordination number of water 22 , and also to an increase in the diffusion coefficient at low temperatures 23 , but at high temperatures the effect of the pressure on the diffusion coefficient is the opposite. Indeed, when the high pressure is applied, the diffusion coefficient of water and methanol (data not shown) decrease by about 40% and 50%, respectively.…”
Section: Coordination and Excess Coordination Numbersmentioning
confidence: 99%